Test-retest reliability of upper-limb proprioception and balance tests in older nursing home residents - Galhardas, L; Raimundo, A; Marmeleira, J (My University, 2020)
Aim To examine the test-retest reliability of two upper-limb proprioception tests (Weight Detection Test, or WDT, and Arm Ruler Positioning Test, or ARPT) and two balance tests (Functional Reach Test, or FRT, and Timed Up and Go test, or TUG) in older nursing home residents. Methods Fifty-three nursing home residents (85.9 ± 3.9 years) participated in this study. Outcome measures were assessed on two occasions, 10–14 days apart. The same rater administered all tests. The relative reliability was estimated using the intraclass correlation coefficients (ICCs) with a two-way mixed-effects model. The absolute reliability was analyzed using the standard error of the mean (SEM) to estimate the minimal detectable change (MDC) at the 95 % confidence level. Systematic bias was studied using the paired-samples t-test or the Wilcoxon signed-rank test. Results The WDT (ICC = 0.84), ARPT (ICC = 0.87) and FRT (ICC = 0.85) had good relative reliability, and the TUG (ICC = 0.99) had excellent reliability. Our results suggest acceptable measurement precision: the SEMs were equal to 1.0 points, and 0.3 cm, 1.5 cm, and 0.5 s for the WDT, ARPT, FRT, and TUG, respectively. The mean difference between sessions was 0.3 points (1.4 %; w=-1.37, p = 0.17) in the WDT, 0.1 cm (-0.74 %; t = 0.41, p = 0.68) in the ARPT, 0.1 cm (0.45 %; w=-0.33, p = 0.74) in the FRT, and 0.2 s (1.37 %; w=-2.28, p = 0.02) in the TUG. Conclusions This study showed that the four field-usable motor tests had good to excellent test-retest reliability and had acceptable measurement precision in older nursing home residents. These tests could be valuable clinical tools for assessing proprioception and balance in nursing home residents.
Keywords: reliability; proprioception tests; balance tests; nursing home residents